Социально-психологические особенности развития и обучения взрослых - Зинченко, Светлана; Котырло, Тамара (Զանգակ հրատ.)
The authors consider the problem of the adult social and psychological development and education. It analyzes various directions of social and psychological development, the peculiarities of the institutional type of training, as well as the basis of forms of training of adult education.
Keywords: Методика обучения и преподавания